Implementasi Canva Dalam Peningkatan Pembelajaran di SDN Gabahan - Anita Fira Waluyo; Irma Handayani; Ikrima Alfi; Wahyu Sri Utami; Anna Dina Kalifia; Selfi Artika (Universitas Teknologi Yogyakarta, 2025)
The main challenge faced by educators in the current digital era is creating interesting and informative learning materials. Graphic design plays an important role in creating effective learning materials. As an easy-to-use graphic design platform, Canva can be an effective solution to meet these needs. Using Canva in graphic design to create learning materials is a community service that aims to improve the quality of learning materials by utilizing the Canva graphic design platform. This research aims to provide tools and knowledge for educators in creating interesting and informative learning materials. This training was carried out using interactive lecture methods, direct practice and question and answer. The measurement of the results achieved is an increase in educators' skills and understanding in using Canva for graphic design. This is proven by the quality of the learning materials produced after the training. Evaluation of the learning materials that have been created also shows improvements in visual appeal, message clarity and overall learning effectiveness. Thus, the use of Canva in graphic design for creating learning materials has had a positive impact in improving the quality of learning and students' learning experiences.